The ECB survey of professional forecasters (SPF) – A review after eight years' experience - Carlos Bowles; Roberta Friz; Veronique Genre; Geoff Kenny; Aidan Meyler; Tuomas Rautanen (European Central Bank (ECB), 2007)
Eight years have passed since the European Central Bank (ECB) launched its Survey of Professional Forecasters (SPF). The SPF asks a panel of approximately 75 forecasters located in the European Union (EU) for their short- to longer-term expectations for macroeconomic variables such as euro area inflation, growth and unemployment. This paper provides an initial assessment of the information content of this survey. First, we consider shorter-term (i.e., one- and two-year ahead rolling horizon) forecasts. The analysis suggests that, over the sample period, in common with other private and institutional forecasters, the SPF systematically under-forecast inflation but that there is less evidence of such systematic errors for GDP and unemployment forecasts. However, these findings, which generally hold regardless of whether one considers the aggregate SPF panel or individual responses, should be interpreted with caution given the relatively short sample period available for the analysis. Second, we consider SPF respondents' assessment of forecast uncertainty using information from heir probability distributions. The results suggest that, particularly at the individual level, SPF respondents do not seem to fully capture the overall level of macroeconomic uncertainty. Moreover, even at the aggregate level, a more sophisticated evaluation of the SPF density forecasts using the probability integral transform largely confirms this assessment. Lastly, we consider longer-term macroeconomic expectations from the SPF, where, as expectations cannot yet be assessed against so few actual realisations, we provide a mainly qualitative assessment. With regard to inflation, the study suggests that the ECB has been successful at anchoring longterm expectations at rates consistent with its primary objective to ensure price stability over the medium term. Long-term GDP expectations – which should provide an indication of the private sector's assessment of potential growth – have declined over the sample period and the balance of risks reported by respondents has generally been skewed to the downside.
Keywords: 330; Wirtschaftsprognose; Prognoseverfahren; Vergleich; EU-Staaten